Nomogram to predict lymph node metastasis in patients with early oesophageal squamous cell carcinoma. Issue 11 (4th June 2018) - Zheng, H; Tang, H; Wang, H; Fang, Y; Shen, Y; Feng, M; Xu, S; Fan, H; Ge, D; Wang, Q; Tan, L
Abstract: Background: Lymph node status is crucial in determining the prognosis for early oesophageal squamous cell carcinoma (SCC). This study aimed to develop and validate a nomogram for the prediction of lymph node metastasis in patients with early SCC. Methods: A prediction model was developed in a derivation cohort of patients with clinicopathologically confirmed early SCC. Patients who underwent oesophagectomy for pT1 SCC between January 2010 and December 2013 were identified from an institutional database. Risk factors for lymph node metastasis were assessed using a binary logistic regression modelling technique. A nomogram for the prediction of lymph node metastasis was constructed using the results of multivariable analyses. For internal validation, bootstraps with 1000 resamples were performed. The predictive performance of the nomogram was measured by Harrell's concordance index (C-index). An independent cohort from the same hospital was used to validate the nomogram. This cohort included consecutive patients with early SCC who underwent oesophagectomy from January 2014 to December 2015. Results: The derivation cohort included 281 patients. Four variables associated with lymph node metastasis were included in the model: depth of tumour invasion (odds ratio (OR) 4·37, 95 per cent c.i. 1·59 to 12·03; P = 0·004), grade of differentiation (OR 4·47, 1·02 to 19·70; P = 0·048), tumour size (OR 2·52, 1·11 to 5·75; P = 0·028) and lymphovascular invasion (OR 6·58, 2·54 to 17·05; P < 0·001). The C-index was 0·790 (95 per cent c.i. 0·717 to 0·864) in the derivation cohort and 0·789 (0·709 to 0·869) for the validation cohort (198 patients). Conclusion: A validated nomogram for patients with early oesophageal SCC can predict the risk of lymph node metastasis. Abstract : Selecting patients for surgery or endoscopic treatment